FAKTOR-FAKTOR YANG MEMPENGARUHI WANITA USIA SUBUR (WUS) MELAKUKAN DETEKSI DINI KANKER SERVIKS METODE PAP SMEAR DI RSUD ARIFIN ACHMAD PEKANBARU TAHUN 2018 - Oktaliza Elektrina; Syamsul Bahri; Oktavia Dewi (Ensiklopedia of Journal, 2020)
One of a disease that can be disrupt reproductive health of the woman is cervical of cancer. The most effective way to prevention the cervical of cancer is through early detection with pap smear methode. The purpose of this research is to know determine of factors that influence women in their reproductive age to do early detection cervical of cancer with pap smear methode. The kind of research is descriptive analytic with case-control approach. The population of this study were 266 woman who divided into 2 groups, 166 cases respondents and 133 control respondents. Data analysis multivariate with regression logistic desain. Based on the results of the multivariate analysis, it was found that variables are associated meaningful with women in their reproductive age do early detection cervical of cancer withpap smear methode is the knowledge variable (0.001), and support of medical health (0.001). While confounding variable in this research is support of husband (0,050). Conclusion : Woman in their reproductive age has knowledge less than good risk not do the pap smear of 2 times larger than woman who is good knowledge. Woman who did not receive support of medical health service risk 2 times larger than woman receive support of medical health. Advice : Established cooperation with related state such as puskesmas and spreading leaflets and educate woman on when they comes to seek health care treatment in order to be more understanding cervical of cancer danger, so that would be willing to investigates the request with pap smear methode.